Synthesis and Antimicrobial activity of 6-Thioxo-6,7-dihydro-2H-[1,2,4]triazino[2,3-c]quinazolin-2-ones Derivatives - Nosulenko, Inna S.; Voskoboynik, Olexii Yu.; Berest, Galina G.; Safronyuk, Sergiy L.; Kovalenko, Sergiy I.; Kamyshnyi, Oleksandr M.; Polishchuk, Nataliya M.; Sinyak, Raisa S.; Katsev, Andrey V. (My University, 2014)
Potassium 8-R1-9-R2-10-R3-3-R-2-oxo-2Н-[1,2,4]triazino[2,3-с]quinazoline-6-thiolates 2.1–2.26 were synthesized via cyclocondensation of 6-R-3-(3-R1-4-R2-5-R3-aminophenyl)-1,2,4-triazin-5-ones 1.1–1.26 with carbon disulfide, potassium hydroxide, and ethanol or with potassium O-ethyl dithiocarbonate in 2-propanol. The corresponding thiones 3.1–3.26 were obtained by treatment of 2.1–2.26 with hydrochloric acid. It was found that the nature of the substituents in positions 3, 4, and 5 of the corresponding 6-R-3-(3-R1-4-R2-5-R3-amino-phenyl)-1,2,4-triazin-5-ones were affected on the terms of the reaction. The structures of compounds were proven by a complex of physicochemical methods (1H, 13C NMR, LC–MS, and EI-MS). The results of the antibacterial and antifungal activity assay allowed the determination of the high sensitivity of Staphylococcus aureus ATCC 25923 (MIC 6.25–100 µg/mL, MBC 12.5–200 µg/mL) to the synthesized compounds.
Keywords: Synthesis; Potassium salt; 6-Thioxo-6,7-dihydro-2H-[1,2,4]triazino[2,3-c]quinazolin-2-one derivatives; Antimicrobial activity